2017
DOI: 10.1186/s40246-017-0120-8
|View full text |Cite
|
Sign up to set email alerts
|

Whole transcriptome analysis of human erythropoietic cells during ontogenesis suggests a role of VEGFA gene as modulator of fetal hemoglobin and pharmacogenomic biomarker of treatment response to hydroxyurea in β-type hemoglobinopathy patients

Abstract: BackgroundHuman erythropoiesis is characterized by distinct gene expression profiles at various developmental stages. Previous studies suggest that fetal-to-adult hemoglobin switch is regulated by a complex mechanism, in which many key players still remain unknown. Here, we report our findings from whole transcriptome analysis of erythroid cells, isolated from erythroid tissues at various developmental stages in an effort to identify distinct molecular signatures of each erythroid tissue.ResultsFrom our in-dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Another study suggests that the vascular endothelial growth factor (VEGFA) gene is a biomarker in β-type hemoglobinopathies severity and efficacy of HU therapy (Chondrou et al, 2017). These findings are in agreement with a study included in this systematic review that found SNPs in the FLT1 gene, encoding VEGF receptor 1, associated with HbF changes by HU therapy in Hb SS patients (Ma et al, 2007).…”
Section: Signaling Pathways Underlying Hbf Changes In Response To Hu Therapysupporting
confidence: 75%
See 2 more Smart Citations
“…Another study suggests that the vascular endothelial growth factor (VEGFA) gene is a biomarker in β-type hemoglobinopathies severity and efficacy of HU therapy (Chondrou et al, 2017). These findings are in agreement with a study included in this systematic review that found SNPs in the FLT1 gene, encoding VEGF receptor 1, associated with HbF changes by HU therapy in Hb SS patients (Ma et al, 2007).…”
Section: Signaling Pathways Underlying Hbf Changes In Response To Hu Therapysupporting
confidence: 75%
“…Three studies did not assess whether the SNPs affected HbF levels (Italia et al, 2010;Zhu et al, 2017;Yahouedehou et al, 2020). Four studies did not differentiate patients with SCA from patients with SCD (Borg et al, 2012;Gravia et al, 2016;Chondrou et al, 2017;Elalfy et al, 2017). One study was part of an oral session and their results were later published in an original article already included in this systematic review (Wyszynski et al, 2004).…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…HU treatment is up-to-date the only approved FDA-treatment for SCD and beta-thalassemia (Chondrou V. et al (2017) 62 . The mechanisms of its HbF induction and its effects on the global transcriptome are not yet fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The molecular machinery involved in human Hb switching has been extensively studied, leading to identification of genetic modifier genes and the defining of the contribution of modifier variants in modulating the phenotypic diversity of b-thalassemia and sickle cell disease by regulating HbF levels. [3][4][5] Two transcription factors (TFs), BCL11A and ZBTB7A/LRF, have been identified as major erythroid-specific HbF repressors, [6][7][8][9] and both have recently been shown to bind cis-acting elements in the g-globin promoter. 10,11 A domainfocused CRISPR screen has identified heme-regulated inhibitor 12 as a potentially druggable target involved in HbF silencing through the regulation of BCL11A.…”
Section: Introductionmentioning
confidence: 99%